Rapid progression of spinal epidural lipomatosis - Choi, Kyung-Chul (Springer-Verlag, 2011)
Spinal epidural lipomatosis (SEL) is a rare but well-recognized condition. In general, the onset of its symptoms is insidious and the disease progresses slowly. We report two cases of rapid progression of SEL with no history of steroid intake in non-obese individuals after epidural steroid injection. These SEL patients developed neurologic symptoms after less than 5 months; these symptoms were confirmed to be due to SEL by serial MR images. After the debulking of the epidural fat, their symptoms improved.